2018
DOI: 10.1159/000492521
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Circulating Tumor Cells in Ovarian Cancer and Their Clinical Value as a Biomarker

Abstract: Background/Aims: Monitoring the appearance and progression of tumors are important for improving the survival rate of patients with ovarian cancer. This study aims to examine circulating tumor cells (CTCs) in epithelial ovarian cancer (EOC) patients to evaluate their clinical significance in comparison to the existing biomarker CA125. Methods: Immuomagnetic bead screening, targeting epithelial antigens on ovarian cancer cells, combined with multiplex reverse transcriptase-polymerase chain reaction (Multiplex R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(74 citation statements)
references
References 43 publications
(52 reference statements)
1
60
0
3
Order By: Relevance
“…Ovarian cancer (OC) is s the seventh most common cancer and a type of gynaecological malignancies, with high mortality in females [1][2][3]. The majority of ovarian cancers (nearly 90%) are originated from epithelial tissues [4,5]. Despite ongoing efforts to find effective treatment methods for OC, the overall survival rate remains less than 30%, which was mainly caused by the difficulty for early diagnosis, and often results in a poor prognosis [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Ovarian cancer (OC) is s the seventh most common cancer and a type of gynaecological malignancies, with high mortality in females [1][2][3]. The majority of ovarian cancers (nearly 90%) are originated from epithelial tissues [4,5]. Despite ongoing efforts to find effective treatment methods for OC, the overall survival rate remains less than 30%, which was mainly caused by the difficulty for early diagnosis, and often results in a poor prognosis [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, the CTC positivity rate declined rapidly during treatment and no patient showed CTCs at the end of sixth cycle of chemotherapy. In the study by Zhang et al, CTC counts decreased during adjuvant and neoadjuvant therapy as well [22]. Interestingly, peripheral blood was obtained both before and 7-14 days after surgery and a rapid increase in CTC counts has been observed between these two time points.…”
Section: Discussionmentioning
confidence: 92%
“…Possibly, not only the presence of CTCs, but their expression profiles may predict the clinical potential. Zhang et al examined blood samples from 109 patients with newly diagnosed ovarian cancer using Multiplex-RT-PCR based on the detection of six cancer-related genes [22]. While this assay yielded very high CTC detection rates of 90%, the survival analysis showed that only EpCAM positivity of CTCs predicted shorter OS.…”
Section: Discussionmentioning
confidence: 99%
“…Following the emergence of this information regarding the potential predictive value of mesenchymal-or mixed E/M-phenotype CTCs, we developed and validated a novel custom CellSearch Âź assay to assess p16 expression in the putative mixed E/M-phenotype subpopulation. Because assay validation was completed during the late stages of this trial, we performed a pilot analysis of putative mixed E/Mphenotype CTCs in 13 of the final patients enrolled, employing MUC1 as a tumor marker as has been done in several prior CTC studies [43][44][45], and enumerating and measuring p16 expression in VIM + , MUC1 + , DAPI + , and CD45cells from peripheral blood specimens. To assess all 5 markers, we implemented and validated a novel 5-color CellSearch Âź assay ( Supplementary Fig.…”
Section: Characterization Of Vimentin-positive Ctcsmentioning
confidence: 99%